The human vice expressed in the Bosch - DOI: 10.4025/actascihumansoc.v31i1.3449 - Oliveira, Terezinha (2009)
The objective of this study is to discuss one of most evidenced themes in the works of Hieronymus Bosch (1450-1516), a master of Dutch painting who lived in the late 15th and early 16th centuries: human vice. His accomplishments are known mainly for depicting a conflict between common life and the look for eternal well-being, beyond the representation of the fears, anguish and desires of the late Middle Ages. Our analysis is based on the main idea that image is an educational resource. Thus, we seek, over the course of the study, to mention human vices as guiding sources for social organization. The development takes place through the relation between themes painted by Bosch and medieval thought.